IDENTIFIKASI LAPISAN RAWAN LONGSOR JALUR REL KERETA API ANTARA STASIUN CICAYUR DAN STASIUN PARUNG PANJANG, BANTEN - Febty Febriani; Titi Anggono; Jauhari Arifin (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
The landslide prone area on the railway between the Cicayur and Parung Panjang stations, Banten, which lie on between the Tanah Abang and Parung Panjang stations, has been investigated. The railway track between Tanah Abang and Parung Panjang stations is the busy track since this track is passed by the commuter lines which have the route from the Bumi Serpong Damai (BSD) Serpong to the Jabodetabek (Jakarta, Bogor, Depok, Tangerang, and Bekasi).  The investigation has been carried out by using direct current resistivity (DC resistivity) method (dipole-dipole and wenner arrays). The dipole-dipole and wenner arrays have 240 m and 20 m electrodes spacing, respectively. The resistivity data have been analyzed by using RES2DInv and IP2WIN programs. The result shows that the study area has low resistivity values (47.13 Î©m) at near surface and is possibly associated with the volcanic and sedimentary material in the study area. The area which consists of the volcanic and sedimentary material will be landslide prone area if the ability of the rock layer to resist the rainfall infiltration has exceeded its threshold.Keyword: railway track, landslide, DC resistivity, RES2DInv, IP2Win.